Associations of birth weight and later life lifestyle factors with risk of cardiovascular disease in the USA: A prospective cohort study. (September 2022) - Wang, Yi-Xin; Li, Yanping; Rich-Edwards, Janet W.; Florio, Andrea A.; Shan, Zhilei; Wang, Siwen; Manson, JoAnn E.; Mukamal, Kenneth J.; Rimm, Eric B.; Chavarro, Jorge E.
Summary: Background: Low birth weight has been associated with a greater risk of cardiovascular disease (CVD). However, the interaction between low birth weight and adult lifestyle factors on the risk of CVD remains unclear. Methods: We included 20, 169 men from the Health Professionals Follow-up Study (HPFS, 1986–2016), 52, 380 women from the Nurses' Health Study (NHS, 1980–2018), and 85, 350 women from the Nurses' Health Study II (NHS II, 1991–2017) in the USA who reported birth weight and updated data on adult body weight, smoking status, physical activity, and diet every 2–4 years. Incident cases of CVD, defined as a combined endpoint of fatal and nonfatal coronary heart disease (CHD) and stroke, were self-reported and confirmed by physicians through reviewing medical records. Findings: During 4, 370, 051 person-years of follow-up, 16, 244 incident CVD cases were documented, including 12, 126 CHD and 4118 stroke cases. Cox proportional hazards regression models revealed an increased risk of CHD during adulthood across categories of decreasing birth weight in all cohorts (all  P  for linear trend <0.001). Additionally, we found an additive interaction between decreasing birth weight and unhealthy lifestyles on the risk of CHD among women, with a pooled relative excess risk due to interaction of 0.06 (95% CI: 0.04–0.08). The attributable proportions of the joint effect were 23.0% (95% CI: 11.0–36.0%) for decreasing birth weight alone, 67.0% (95% CI: 58.0–75.0%) for unhealthy lifestyle alone, and 11.0% (95% CI: 5.0–17.0%) for their additive interaction. Lower birth weight was associated with a greater stroke risk only among women, which was independent of later-life lifestyle factors. Interpretation: Lower birth weight may interact synergistically with unhealthy lifestyle factors in adulthood to further increase the risk of CHD among women. Funding: The National Institutes of Health grants.